Peran dan Fungsi Otoritas Jasa Keuangan Dalam Melindungi Konsumen Melalui Penyelidikan dan Penyidikan Tindak Pidana Perbankan : Studi Kasus Bank Perkreditan Rakyat Nusa Galang Makmur, Deli Serdang - Teuku Fathir Mustafa; Bismar Nasution; Sunarmi Sunarmi; Muhammad Ekaputra (USU LAW JOURNAL, 2019)
Abstract. In carrying out its duties and authorities based on independence and free from the intervention of any party, one of the tasks of the OJK is "Investigation" which is one of the OJK supervisory duties as referred to in Article 9 letter c of Law No. 21 of 2011 concerning the Financial Services Authority. If the occurrence of a criminal offense in the banking sector is carried out by an insider, there are several laws that are usually applied, namely: The Criminal Code, for example: Counterfeiting, Darkening, Emphasis in Position, Deception, and Theft, etc Law No. 31 of 1999 concerning Eradication of Corruption Crime as amended by Law No. 20 of 2001 concerning Amendments to Law No. 31 of 1999 concerning Eradication of Corruption Crime; and Law No. 7 of 1992 concerning Banking as amended by Law No. 10 of 1998 concerning Amendment to Law No. 7 of 1992 concerning Banking. The Financial Services Authority is expected to be able to realize a financial system that grows sustainably and stably and is able to protect the interests of consumers and society. Article 29 paragraph (1) Law No. 8 of 1999 concerning Consumer Protection, that the government is responsible for fostering the implementation of consumer protection which guarantees the rights of consumers and business actors and the obligations of consumers and business actors. The case of banking crime that was raised in this study is the allegation of "Banking Crimes at PT. BPR Nusa Galang Makmur, Deli Serdang North Sumatra ", which was allegedly carried out by the Managing Director of PT. BPR Nusa Galang Makmur. The President Director intentionally provided credit facilities to 34 debtors of Rp. 3,210,000,000, - which deviates from the banking provisions.   Keywords       :     financial services authority, consumer protection, banking crimes.